Mathematical Numeracy Literacy Ability of High School Students in Solving Math Problems - Ladyawati, Erlin; Maftuh, Moh. Syukron (Universitas Negeri Surabaya, 2025)
As the low mathematical connection problem shows, students are unable to make mathematical connections on their own. Thus the ability to make mathematical connections is very necessary for training students. This study aims to describe students' mathematical numeracy literacy skills using AKM questions with adapted PISA standards and the difficulties faced by students in solving the given questions. The subjects of this study were grade XI students of SMA Wachid Hasyim 2 Taman Sidoarjo who were selected in one class with a total of 28 students. The type of research used in this study is Mixed Methods Research. The techniques used in this study are test techniques to determine students' ability to solve math numeracy literacy problems, questionnaire techniques to find out students' difficulties, and interviews for in-depth examinations. From the results of the study, it was found that level 1 and 2 category questions were very good, students were able to provide explanations in the form of mathematics and use simple procedures to solve problems. In level 3 and 4 category questions are sufficient, students are still able even though they are not optimal in understanding concepts, representing, and designing solving strategies. On the level 5 question, the category is less. This is because students are less able to represent, reflect, and communicate questions properly and correctly. Level 6 category questions are lacking because students have not been able to apply and master technical mathematical operations, develop new strategies and approaches to deal with new situations, and communicate well. The biggest difficulty faced by students is in analyzing problems, representing, designing solving strategies, accuracy of calculations, and communicating them with argumentation.